PENGARUH HARGA, KUALITAS PRODUK, LOKASI DAN FASILITAS TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN DE MUTIARA BATAM - Jecky; Riki (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to determine and examine the effect of price, product quality, location and facilities on purchasing decisions for housing De Mutiara Batam. Data collection was carried out by distributing online-based questionnaires and with a total of 37 respondents. In this study using the Non Probability Sampling method with purposive sampling technique. This research uses descriptive quantitative method, using several tests namely validity test, reliability test, classical assumption test, multiple linear regression, t test, f test and coefficient of determination. Data analysis using the IBM Statistic 20 version of the SPSS program, in the results of this study, the regression equation Y = 8.197 + -(0.073)X1 + 0.052X2 + 0.095X3 + 0.310X4 + e, the price variable has a negative effect between price on purchasing decisions and tcount ( -0.0593) <t table (2.03693). The product quality variable has a positive influence between product quality on purchasing decisions with tcount (0.451) <(2.03693). The location variable has a positive influence between location on purchasing decisions with tcount (0.868) <(2.03693). Facility variable has a positive influence between facilities on purchasing decisions with a value of tcount (1.728) <(2.03693). As well as the variable price, product quality, location and facilities on purchasing decisions simultaneously do not affect the purchase decision (Y) with the value of Fcount = 1.961 <Ftable = 2.66